Executive Summary: Digitally integrated approaches for managing climate risk and increasing food security - CGIAR Research Program on Climate Change, Agriculture and Food Security; Alliance of Bioversity International and CIAT (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Oftentimes, we rely on what our local meteorologists tell us about the weather for any given day or the climate for the next few months. But, how well can we forecast weather and climate? And what can we do with these forecasts? Agricultural climate services (CS) involve the generation, translation, transfer, and use of climate knowledge and information. We deliver site-specific, reliable climate information to farmers (understanding the past and projecting relevant information on the future) in a demand-driven and timely manner, to enable better informed farming decisions